2022
DOI: 10.1186/s40360-022-00557-7
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan alleviates arsenic-induced hepatotoxicity in mice via downregulation of OX40/IL-17A and activation of Nrf2 signaling

Abstract: Background Arsenic, existing ubiquitously in soil, drinking water, or food, is well known to be an environmental pollutants concerned by European Food Safety Authority. Lentinan, a beta-1,6;1,3-glucan extracts from Lentinus edodes, which has the properties of antioxidant and immunomodulation, present study explored the pharmacological effects of Lentinan on arsenic induced hepatotoxicity in mice. Methods Mice experiments were performed by sodium ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…When oxidative stress occurs in the human body, Nrf2 is released from Keap1, enters the nucleus, and interacts with the antioxidant response element (ARE) [ 59 ]. Lentinan (LNT) activated the Nrf2 pathway and inhibited hepatocyte oxidative stress [ 60 ]. Polysaccharides can induce the expression of antioxidant genes or proteins and improve antioxidant effects through the Nrf2/ARE pathway.…”
Section: Biological Activity Of Polysaccharidesmentioning
confidence: 99%
“…When oxidative stress occurs in the human body, Nrf2 is released from Keap1, enters the nucleus, and interacts with the antioxidant response element (ARE) [ 59 ]. Lentinan (LNT) activated the Nrf2 pathway and inhibited hepatocyte oxidative stress [ 60 ]. Polysaccharides can induce the expression of antioxidant genes or proteins and improve antioxidant effects through the Nrf2/ARE pathway.…”
Section: Biological Activity Of Polysaccharidesmentioning
confidence: 99%
“…OX40, named CD134 or tumor necrosis factor receptor superfamily member 4 (TNFRSF4), is defined as a biomarker of T cell activation capable of increasing pro-inflammatory cytokines [28]. The latest study found that LNT can downregulate OX40/IL-17A signaling and activate nuclear factor erythroid 2 related factor (Nrf2), an important factor in oxidative stress [29].…”
Section: Studies Of Lnt In Inflammation Of Intestinal Inflammationmentioning
confidence: 99%
“…It was demonstrated that ursodeoxycholic acid expresses protective effects against arsenic induced hepatotoxicity through Nrf2 (nuclear factor erythroid 2 -related factor 2) signalling pathway (Li et al, 2020). Recently, pharmacological effects of lentinan, αβ -1,6;1,3 glucan extract from Lentinus edodes which has antioxidant and immune-modulating properties, have been studied in mice (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%